40. The International Learning Object Metadata Survey - Friesen, Norm (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
A wide range of projects and organizations is currently making digital learning resources (learning objects) available to instructors, students, and designers via systematic, standards-based infrastructures. One standard that is central to many of these efforts and infrastructures is known as Learning Object Metadata (IEEE 1484.12.1-2002, or LOM). This report builds on Report #11 in this series, and discusses the findings of the author's recent study of ways in which the LOM standard is being used internationally.